Mathematical modelling of integration effects using the example of the EAEU - Gospodarik, Catherine G.; Kovalev, Mikhail M. (Journal of the Belarusian State University. Economics, 2023)
The article analyses and develops the mathematical apparatus for measuring the effectiveness of regional and global economic integration. Various models for calculating the effects of integration are considered: models of global integration, models of composite indices for measuring the degree of economic integration in the association, models of the significance of the integration association in the world, interregional integration models based on input – output model (V. V. Leontief), models of collective economic security of the integration association, gravitational models of mutual trade, econometric models of economic growth of countries taking into account integration effects, regression models of the impact of economic integration on GDP growth, models for assessing the impact of integration on the growth of aggregate factor productivity. The author’s system of models for comparative analysis of the dynamics of the speed of integration of countries into a regional association is introduced. A data envelopment model (model DEA) is proposed to measure the comparative evaluation of integration efficiency. Attention is focused on the selection of indicators for assessing the effects for the combined economic systems and assessing the significance of the integration association in the world.
Keywords: economic integration; efficiency of unification; econometric model; gravitational model of trade; Leontief model; data envelopment model (model DEA); Eurasian Economic Union; European Union; Association of Southeast Asian Nations; composite indices; economic growth